Numerical Study on the Motion and Wave Loads of an Uncrewed Surface Vehicle Catamaran at Low Speed in Sea Waves - T. T. Nguyen; T. L. Phan; T. H. Le (Journal of Applied Fluid Mechanics)
Modern ship designs are being developed for various purposes in uncrewed operation. In particular, low-speed uncrewed surface vehicle (USV) catamarans have been applied as rescued boats in recent years. Therefore, predicting the performance of this ship type in calm water and waves is necessary. This study investigates the response, shear force, and bending moment of a low-speed USV catamaran operating in regular and irregular waves. Numerical simulations are conducted using the Ansys AQWA solver, which employs the boundary element method to model inviscid flow. The catamaran’s responses in regular waves, with the ratio of wavelength to ship length ranging from 0.4 to 2.0, are compared with the experimental data. The catamaran’s behavior in irregular waves is then determined from integrating its responses in regular waves over the encounter wave spectrum. Additionally, the catamaran’s responses and the wave-induced vertical shear force and the bending moment at the x- and y-axes within a frequency range of 0.2 to 3.0 rad/s are analyzed. We demonstrated that the heave, roll, and pitch of the catamaran align well with the corresponding experimental data. Significant vertical shear forces are observed at a wavelength-to-ship-length ratio of 1.0, particularly at one-fourth of the ship's length from either end. The transverse bending moment is significant in a wide range of wave frequencies for the ship in beam seas. The findings show that the maximum midship vertical bending moment in the frequency range of 1.5 to 3.0 when the ship moves in head waves should be considered. The vertical shear force and transverse midship bending moment in the whole frequency domain should be assessed when the catamaran operates in  beam waves.